PERANCANGAN TATA LETAK GUDANG PRODUK JADI CAT DENGAN METODE DEDICATED STORAGE DI PT. AKZONOBEL CAR REFINISHES INDONESIA - SUWARNO SUWARNO; BASUKI ARIANTO; KAREL L. MANDAGIE (JURNAL TEKNIK INDUSTRI, 2021)
PT. Akzonobel Car Refinishes Indonesia is a car paint factory located in East Jakarta that has a finished warehouse located in the area of the factory. The problems faced are irregularities in the laying of products, this will hamper the search process and movement which is quite high so that the use of space becomes less effective and many are not in accordance with the warehouse layout system, it will be improved warehouse layout with Dedicated storage method. This research was conducted by collecting data on warehouse area, box dimensions on each product, material handling dimensions, car paint product data in the period OctoberDecember 2018. Then calculating the development of warehouse needs which included storage space requirements, warehouse area, activity retrieval of goods, distance calculation by rectilinear distance method and classification of goods based on the frequency of ABC analysis. The results of the analysis and discussion of the new warehouse with the dedicated storage method and the results of ABC analysis classifications consisting of classification A: Clear, Putty, and Thiner, while classification B: Hardener and classification C: Toner. The mileage calculation of material handling processes becomes more efficient, which is reduced from 58,065m / month to 46,440m / month or there is efficiency of 20.02%.Keywords: Dedicated Storage Method, Warehouse Layout, Rectilinear Distance